Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1161/circulationaha.106.625475
|View full text |Cite|
|
Sign up to set email alerts
|

Five-Year Follow-Up of the Medicine, Angioplasty, or Surgery Study (MASS II)

Abstract: Background-Despite routine use of coronary artery bypass graft (CABG) and percutaneous coronary intervention (PCI), no conclusive evidence exists that either modality is superior to medical therapy (MT) alone for treating multivessel coronary artery disease with stable angina and preserved ventricular function. Methods and Results-The primary end points were total mortality, Q-wave myocardial infarction, or refractory angina requiring revascularization. The study comprised 611 patients randomly assigned to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(88 citation statements)
references
References 20 publications
(14 reference statements)
5
77
1
5
Order By: Relevance
“…These findings likely represent the reported 30-day and 1-, 3-, and 5-year mortality rates of 7.1%, 15%, 22.1%, 18 and 30%, respectively, for thoracic aortic aneurysm surgery, 19 and the reported 4-6%, 20 5-8% 21 15%, 22 and 20% mortality rates for cardiac valve surgery. 23,24 The long-term mortality rate in this study (∼20%) is in accord with published data in patients undergoing CV surgery 18 -26 and may be linked to the associated excess comorbidities, toxicities, and adverse pathobiological states that accelerate cardiovascular damage. 27 Consistent with data from other studies, 8,13,14 patients with AKI following cardiac surgery had reduced long-term cumulative survival compared to those with no AKI, and this was irrespective of nesiritide status.…”
Section: Discussionsupporting
confidence: 87%
“…These findings likely represent the reported 30-day and 1-, 3-, and 5-year mortality rates of 7.1%, 15%, 22.1%, 18 and 30%, respectively, for thoracic aortic aneurysm surgery, 19 and the reported 4-6%, 20 5-8% 21 15%, 22 and 20% mortality rates for cardiac valve surgery. 23,24 The long-term mortality rate in this study (∼20%) is in accord with published data in patients undergoing CV surgery 18 -26 and may be linked to the associated excess comorbidities, toxicities, and adverse pathobiological states that accelerate cardiovascular damage. 27 Consistent with data from other studies, 8,13,14 patients with AKI following cardiac surgery had reduced long-term cumulative survival compared to those with no AKI, and this was irrespective of nesiritide status.…”
Section: Discussionsupporting
confidence: 87%
“…The CABG surgery presents low morbidity and mortality and has safe and reliable late outcomes 9,10 . However, the surgical aggression caused by the sternotomy and by on-pump surgeries results in longer hospital stay duration, mainly due to the PO pulmonary dysfunction 11 .…”
Section: Discussionmentioning
confidence: 99%
“…• analysis was conducted on an intention-to-treat basis (even though 40% of the medical group crossed over to CABG); • only 10% of CABG patients received an internal thoracic artery (ITA); however the most important prognostic component of CABG is the use of one [47,48] [53]. Most patients in these RCTs actually had normal LV function with single or double vessel CAD and without proximal LAD disease.…”
Section: Coronary Artery Bypass Grafting Vs Medical Therapymentioning
confidence: 99%
“…Meta-analyses of these RCTs reported that CABG resulted in up to a five-fold reduction in the need for reintervention, with either no or a modest survival benefit or a survival benefit only in patients >65 years old (HR 0.82) and those with diabetes (HR 0.7) [29]. The 5-year follow-up of the MASS II [53] study of 611 patients (underpowered) reported that the composite primary endpoint (total mortality, Q-wave MI, or refractory angina requiring revascularization) occurred in 36% of OMT, 33% of PCI and 21% of CABG patients (P = 0.003), with respective subsequent revascularization rates of 9%, 11% and 4% (P = 0.02).…”
Section: Coronary Artery Bypass Grafting Vs Medical Therapymentioning
confidence: 99%